2014
DOI: 10.33225/jbse/14.13.608
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Multimedia Learning Material on Students’ Academic Achievement and Attitudes Towards Science Courses

Abstract: This study implemented multimedia learning material developed for the 5th grade science course topic "Food and Healthy Nutrition" and examined its effect on students' academic achievement and science attitudes. The study used a control group, a pre-test-post-test quasi experimental research design, and a convenience sample consisting of 62 5th grade students. The research instruments were an achievement test and a science attitude scale. During the implementation process the experiment group learned using mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…In line with Aloarini's research above, in the context of science learning, Ercan [4] shows that the use of multimedia teaching materials has a significant positive impact on academic achievement and better attitudes of learners towards learning materials. In line with this, Ginns [5] specifically found that the use of learning materials in the form of a combination of pictures and narrated text facilitated good learning compared to learning only using a combination of pictures and written text.…”
Section: Impact On Learning Achievementsupporting
confidence: 69%
“…In line with Aloarini's research above, in the context of science learning, Ercan [4] shows that the use of multimedia teaching materials has a significant positive impact on academic achievement and better attitudes of learners towards learning materials. In line with this, Ginns [5] specifically found that the use of learning materials in the form of a combination of pictures and narrated text facilitated good learning compared to learning only using a combination of pictures and written text.…”
Section: Impact On Learning Achievementsupporting
confidence: 69%
“…Rante [15] stated that the learning outcomes of the students with the use of audio-video based multimedia on the electric dynamic experiment in the classical was said complete learning and learning disabilities more practice and effective. Research of Erchan [5] concluded that multimedia learning promotes more effective learning in science education. The multimedia was developed to improve information and data for their inquiry learning [14].…”
Section: The Video-assisted Inquiry Modified Learning Model On Achiev...mentioning
confidence: 99%
“…On the subject of mechanics there are constraints in terms of experiments, such as nonlinear mechanical vibrations, particle motion in 1, 2 and 3 dimensions, particle motion in 2 and 3 dimensions is constrained, and systems of many particles [11][12][13]. Whereas in terms of solving mathematical models there are constraints, such as linear mechanical vibrations N degrees of freedom, nonlinear mechanical vibrations, constrained particle motion in 2 and 3 dimensions, manyparticle systems, analysis of rigid bodies for inhomogeneous bodies and arbitrary shapes, and gravitational fields by non-homogeneous objects and arbitrary shapes [5]. From the results of observations made at the Faculty of Engineering, University of Medan Area, it was obtained; average midterm exam results on physics and physics lecturers always remind the use and mastery with simple modeling.…”
Section: Introductionmentioning
confidence: 99%